If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -8x = 6 + -4x Solving 2 + -8x = 6 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 2 + -8x + 4x = 6 + -4x + 4x Combine like terms: -8x + 4x = -4x 2 + -4x = 6 + -4x + 4x Combine like terms: -4x + 4x = 0 2 + -4x = 6 + 0 2 + -4x = 6 Add '-2' to each side of the equation. 2 + -2 + -4x = 6 + -2 Combine like terms: 2 + -2 = 0 0 + -4x = 6 + -2 -4x = 6 + -2 Combine like terms: 6 + -2 = 4 -4x = 4 Divide each side by '-4'. x = -1 Simplifying x = -1
| 9z-z=-3+2z-2-7 | | 3*144= | | .2x-3=2 | | -(7x-7y-7)= | | -1x+2y=23 | | -7x+-6x=-12+x+-2X | | X-11+5x=13+6x+2 | | 3x=7x-11 | | -x-5=x-19 | | -7+x-7-2x=-3x+3 | | 8x-(2x+7)=-9x-2(4x+3) | | -6m-5=-17 | | 5-3(w+4)=-10(r-3) | | 7x-5-x=-1-6x+6-3x | | -9d-4+3d=27 | | 59-9x=149 | | -3x^2+7x-6=0 | | m=r-w | | 1+3(r-1)=-2-3r | | c=800-50x+0.25x^2 | | 1.5x+14=42 | | 2x+1+X-1=5 | | (3x+2)10=140 | | 9a-3(2a-x)=20 | | 8z+9-5z=81-5z | | 24=-2x+10x+8 | | 14+6-8=18 | | 3x-5+2x-4=26-2x | | .5(48+24b)=2(17-4b) | | 14x-4x=9x | | 0=-16t^2+70t+9 | | C(v)=0.004v^2-0.62v+30 |